Azolla pinnata as unconventional feeds for ruminant feeding - Soad El Naggar; Hany S. El-Mesery (Bulletin of the National Research Centre, 2022)
Abstract Due to the scarcity of concentrate and green fodder and its high prices in animal feeding, the quest for readily available and inexpensive alternative sources has become critical for breeders seeking to minimize the cost of animal production. Azolla is an invasive plant that grows faster in freshwater lakes, rivers, wetlands, and ditches in both temperate and tropical countries by a few precautionary steps with low production costs. It can modify biodiversity and aquatic ecosystems substantially. Azolla has a symbiotic relationship with the nitrogen-fixing blue-green alga Anabaena azollae, which increases the protein content of Azolla, making it one of the greatest alternative feed ingredients as a source of protein, with 25–30% protein, 7–10% amino acids, vitamins (Beta Carotene, vitamin A, vitamin B12), minerals (calcium, potassium, phosphorus, ferrous, magnesium, copper, etc.), and antioxidants. Several studies showed that Azolla can be fed to animals like cow, buffalo, sheep, goat and rabbit because it is easily digestible (because to its high protein and low lignin content), increases feed efficiency, average daily gain of animals, and milk production by 15–20%. Therefore, the present review was aimed to show the possibility of using Azolla as a source of alternative low-cost protein and its impact on animal efficiency.